1997
DOI: 10.2337/diacare.20.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia: Incidence and Clinical Predictors in a Large Population-Based Sample of Children and Adolescents with IDDM

Abstract: Newly diagnosed children appear to be protected from severe hypoglycemia. Rates increase with lower glycated hemoglobin, especially when mean HbA1c is < 8.0%. Younger children, who may be more susceptible to the adverse effects of neuroglycopenia, are at a particular risk of significant hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
177
4
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(205 citation statements)
references
References 13 publications
15
177
4
9
Order By: Relevance
“…Of the 585 patients, 186 experienced a total of 477 severe episodes with a total follow-up time of approximately 3,500 patientyears. The overall incidence rate of 14.0 per 100 patientyears is similar to the rate we have reported previously [2,22] and comparable with other studies [1,29,30]. A Swedish study reported an overall incidence rate of 17.0 per 100 patient-years [20], which is slightly higher than our study, and a median age of 12.8 years compared with 10 years in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of the 585 patients, 186 experienced a total of 477 severe episodes with a total follow-up time of approximately 3,500 patientyears. The overall incidence rate of 14.0 per 100 patientyears is similar to the rate we have reported previously [2,22] and comparable with other studies [1,29,30]. A Swedish study reported an overall incidence rate of 17.0 per 100 patient-years [20], which is slightly higher than our study, and a median age of 12.8 years compared with 10 years in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Longitudinal clinical data on these patients were collected prospectively from the time of diagnosis of diabetes. Princess Margaret Hospital is the only paediatric diabetes referral centre for diabetes in Western Australia, and all diagnosed children in the state are registered and treated there, thus achieving a 99% case ascertainment rate [22,23] with a very low drop-out rate (<4%). Western Australia has an estimated total population of approximately two million.…”
Section: Subjectsmentioning
confidence: 99%
“…The night period, in particular, remains challenging with over 50% of severe hypoglycemic episodes occurring during sleep in children and adolescents [3]. An assembly of aggravating factors including reduced frequency of blood glucose self-monitoring, blunted sympathoadrenal response to falling blood glucose concentration, reduced hypoglycemia awareness, and reduced warning symptoms and arousal from sleep explain the propensity to nocturnal hypoglycemia [4].…”
Section: Introductionmentioning
confidence: 99%
“…An assembly of aggravating factors including reduced frequency of blood glucose self-monitoring, blunted sympathoadrenal response to falling blood glucose concentration, reduced hypoglycemia awareness, and reduced warning symptoms and arousal from sleep explain the propensity to nocturnal hypoglycemia [4]. Children and adolescents may be more likely to experience hypoglycemic seizures at nighttime [3]. Fear of hypoglycemia is the major barrier to therapy intensification [3], being also a major source of stress and anxiety for families and caregivers [5], affecting quality of life and psychological well-being of the young and families, and leading to suboptimal glucose control [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation